TECHNIQUE AND RESULTS OF RESEARCH OF SOME PARAMETERS OF GRAIN WEIGHT AT ITS MOVEMENT IN A GAP OF A THRESHER OF A COMBINE HARVESTER - A.A. LYASHENKO; O.N. KOSILOV (Advanced Engineering Research, 2008)
To cite data technique and results of research of speed of movement and the sizes of portions of grain weight on the basis of records of oscillograms of efforts of compression moving in a gap of a thresher of a grain stream.